Análise de topologias de inversores integrados monofásicos empregando conversores zeta e cuk - Dionizio, Anderson Aparecido (2023)
This master's thesis presents the study and analysis of three distinct topologies of integrated single-phase inverters, which can operate in autonomous systems or as interface converters between the photovoltaic (PV) generation system and the single-phase alternating current (AC) distribution grid. The first topology, named as I2ZM, is based on the association of two modified Zeta converters. The second structure, named as ICIM, is formed by the association of modified DC/DC Ćuk converters. The third topology, named as IHZC, integrates the characteristics of Zeta and Ćuk converters. The integrated inverters under review employes four power switches associated in series with four power diodes, guarantying uniderectional current flow. Among the four switches, two of them operate on the positive half-cycle of the AC output, while the other two operate on the negative half-cycle. According g the operation of the power switches, it is possible to model the structure by means of an equivalent electrical circuit, which presents static and dynamic behavior similar to that of its traditional DC/DC converters. The design of the integrated topologies under analysis makes them operate in discontinuous conduction mode, presenting three stages of operation for each switching period. In this context, the study of the behavior of voltages and currents for the main components used to implement topologies highlights the differences, advantages, and disadvantages between the integrated inverters. The mathematical equation determines the respective transfer functions of the integrated inverters, which can be analyzed and compared to each other. From the equation of topologies and their respective transfer functions, Proportional- Integral controllers are tunning to control the output voltage in the autonomous system and the output current when operating as an interface converter between a PV arrays and the mains. When the topologies are employed in autonomous systems, theirs output voltage are controlled by a single voltage loop, which acts directly on the duty cycle used in the integrated inverter, requiring a reduced number of sensors. On the other hand, when the topologies are used for grid-connected systems, a multi-loop control strategies are adopted, formed by an external voltage loop, responsible for extracting the maximum power available in the PV array. In contrast, the internal loop is responsible for controlling the current to be injected into the mains. For the synchronization between the output current of the inverters with the mains voltage, a phase locked loop (PLL) system is employed, while the tracking of the maximum power point of the PV arrays is performed by the Perturb and Observe algorithm (P&O). By means of simulations and experimental results, the feasibility and performance of integrated inverter topologies are analyzed and evaluated, as well as the topologies are compared to each other through the analysis of power quality criteria, such as total harmonic distortion (THD) of the output voltage when operating in stand-alone systems and the THD of the injected current for grid-connected systems.